2013
DOI: 10.1590/s0104-14282013005000009
|View full text |Cite
|
Sign up to set email alerts
|

AFM and XRD characterization of silver nanoparticles films deposited on the surface of DGEBA epoxy resin by ion sputtering

Abstract: Abstract:In this work, silver atoms were deposited by ion sputtering on the surface of diglycidyl ether of bisphenol A (DGEBA) epoxy resin cured at 150 °C for 6 hours in air. The films of DGEBA and its precursors were characterized by Raman spectroscopy to identify the main functional groups and their relationship with the deposited silver atoms. Silver thin films of 5, 10, 15 and 20 nm were deposited on the epoxy resin at room temperature. Both the initial film of DGEBA and the subsequent silver thin film wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…526 AFM and XRD were jointly used to characterize Ag NP films, where both techniques provided complementary information. 527 In particular, AFM allowed the characterization of the grain size and the nanoparticle coverage of the surface, while XRD identified the preferential growth direction of the particles. Interestingly, at higher NP coverage, AFM showed that the film was made of larger particle grains.…”
Section: Microscopy Techniques For Np Characterizationmentioning
confidence: 99%
“…526 AFM and XRD were jointly used to characterize Ag NP films, where both techniques provided complementary information. 527 In particular, AFM allowed the characterization of the grain size and the nanoparticle coverage of the surface, while XRD identified the preferential growth direction of the particles. Interestingly, at higher NP coverage, AFM showed that the film was made of larger particle grains.…”
Section: Microscopy Techniques For Np Characterizationmentioning
confidence: 99%
“…9b (curves a and b, respectively). Curve a in this figure shows the regular vibration bands of pure epoxy [44], while that of the CNPs/epoxy composite has one extra permanent band, induced at around 730 cm -1 . This band may be created as a result of bonding between the carbonyl groups which exist in the CNPs (Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 89%
“…Coatings were elaborated by Radiofrequency Magnetron Sputtering, which permits working at low temperature (generally lower than 60 °C). Moreover, the deposits obtained with this technique have a higher density and a better adhesion to the substrate than those elaborated by other methods such as vacuum evaporation [21][22][23] .…”
Section: Introductionmentioning
confidence: 90%